Pathogenetic role of glomerular CXCL13 expression in lupus nephritis. (4th September 2014) - Worthmann, K; Gueler, F; von Vietinghoff, S; Davalos-Mißlitz, A; Wiehler, F; Davidson, A; Witte, T; Haller, H; Schiffer, M; Falk, C S; Schiffer, L
Summary: Podocytes maintain the structure and function of the glomerular filtration barrier. However, podocytes have recently been implicated in the innate immune response, and their function as non-haematopoietic antigen-presenting cells was highlighted. We have shown previously that excessive expression of the chemokine CXCL13 is a distinctive early event for nephritis in a murine model of systemic lupus erythematosus (SLE). Furthermore, we found that CXCL13 is elevated significantly in the serum of patients with SLE-nephritis. In this study, we were able to show for the first time that (i) CXCL13 is expressed locally in glomeruli in a model for SLE-nephritis in mice and that (ii) incubation of human podocytes with CXCL13 induces receptor stimulation of CXCR5 with activation of signalling pathways, resulting in (iii) secretion of proinflammatory cytokines and chemokines in culture supernatant. This cytokine/chemokine cocktail can lead to (iv) a neutrophil respiratory burst in isolated human granulocytes. Taken together, our results provide further evidence that CXCL13 is involved in the pathogenesis of glomerulonephritis and that podocytes can play an active role in local proinflammatory immune responses. Thus, CXCL13 could be a direct target for the therapy of glomerulonephritis in general and for SLE-nephritis in particular.